PEMBELAJARAN DARING PADA PELAJARAN MATEMATIKA SISWA KELAS XI IPA SMA NEGERI 1 TOMOHON - Krista Monika Ransun; Anetha L.F. Tilaar; Nicky Kurnia Tumalun (LPPM Universitas Bina Bangsa, 2023)
Online learning has several challenges such as the internet connection as well as convoluted explanations of math problems which oftentimes affect the capability of teacher to deliver the material optimally. For teachers, weaknesses and potential threats that have been mentioned then become a problem in finding solutions to maintain strengths and opportunities. Thus, the utilization of SWOT analysis was intended to identify all aspects of the application of courageous learning carried out by SMA Negeri 1 Tomohon. The research was conducted to achieve specific objectives, to describe SWOT aspects in the implementation of online learning on math subject in the 11th science class of SMA Negeri 1 Tomohon. The qualitative descriptive method was adapted in this study. The results showed that the implementation of online learning in a SWOT perspective had a correlation with time, costs and economic conditions, unconducive situations, learning resources, and learning motivation as well